2021
DOI: 10.1038/s41591-021-01387-6
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine release syndrome in a patient with colorectal cancer after vaccination with BNT162b2

Abstract: Patients with cancer are currently prioritized in coronavirus disease 2019 (COVID-19) vaccination programs globally, which includes administration of mRNA vaccines. Cytokine release syndrome (CRS) has not been reported with mRNA vaccines and is an extremely rare immune-related adverse event of immune checkpoint inhibitors. We present a case of CRS that occurred 5 d after vaccination with BTN162b2 (tozinameran)—the Pfizer-BioNTech mRNA COVID-19 vaccine—in a patient with colorectal cancer on long-standing anti-P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 28 publications
2
81
0
Order By: Relevance
“…Other data indicate that the effect of N501Y alone on neutralization is relatively modest, and other studies using sera from 20 participants in a trial of the BNT162b2 vaccine showed neutralizing titres equivalent to those of pseudoviruses carrying the N501 and Y501 mutations 82 . Other investigations with recombinant viruses carrying N501Y, ΔH69–V70 + N501Y + D614G or E484K + N501Y + D614G demonstrated that compared with the Wuhan-Hu-1 reference virus, only E484K + N501Y + D614G resulted in a small and modest reduction in neutralization by postvaccination sera elicited by two BNT162b2 doses, and only modest differences in neutralization were seen compared with the Wuhan-Hu-1 reference virus 83 .…”
Section: Vaccine Efficacy Against New Variantsmentioning
confidence: 99%
“…Other data indicate that the effect of N501Y alone on neutralization is relatively modest, and other studies using sera from 20 participants in a trial of the BNT162b2 vaccine showed neutralizing titres equivalent to those of pseudoviruses carrying the N501 and Y501 mutations 82 . Other investigations with recombinant viruses carrying N501Y, ΔH69–V70 + N501Y + D614G or E484K + N501Y + D614G demonstrated that compared with the Wuhan-Hu-1 reference virus, only E484K + N501Y + D614G resulted in a small and modest reduction in neutralization by postvaccination sera elicited by two BNT162b2 doses, and only modest differences in neutralization were seen compared with the Wuhan-Hu-1 reference virus 83 .…”
Section: Vaccine Efficacy Against New Variantsmentioning
confidence: 99%
“…Recent reports described the appearance of SARS-CoV-2 variants harboring mutations within the Spike protein sequence, of which some are associated with increased resistance to mAbs or infectivity 17 – 19 . We decided to evaluate the contribution of mutations within Spike RBD that could influence its interaction with human ACE2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the N501Y mutation has been linked to increased viral infectivity in BALB/c mice 20 , and it has been identified in SARS-CoV-2 variants isolated in UK, South Africa and Brazil. Furthermore, these mutant variants have been reported to be less responsive to recently developed vaccines against SARS-CoV-2 18 , 19 , 21 . However, antibody cocktails could minimize the resistance associated with emerging mutations 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently a case of Citokine Release Syndrome that occurred 5 days after vaccination with BTN162b2 (tozinameran)—the Pfizer-BioNTech mRNA COVID-19 vaccine—in a patient with colorectal cancer was reported [ 23 ].…”
Section: Discussionmentioning
confidence: 99%